Pengaruh Peran Budaya Masyarakat Lokal Terhadap Pemasaran Global - Nisifa Prila Anisa; Nona Ratu Syifa Putri; Mohamad Zein Saleh (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Companies must recognise the culture of the country where the business is targeted. This is because culture is the main element that is very important and has been attached to the community as the intended consumer, so that it can influence his decision to buy a product or use a service that is not in accordance with his culture. This study aims to find out how the role of local community culture in global marketing. The research method used in this study is literature-based research, which is conducting a literature study by collecting data and previous research from various scientific journals, books and current news issues. This research shows that the culture of local people influences purchasing decisions and consumer behavior in the global market, so marketers need to set global marketing strategies.